Secretory Phospholipase A2s in Insulin Resistance and Metabolism - Kuefner, Michael S. (Frontiers in Endocrinology, 2021)
The phospholipases A2 (PLA2) superfamily encompasses enzymes commonly found in mammalian tissues and snake venom. Many of these enzymes have unique tissue distribution, function, and substrate specificity suggesting distinct biological roles. In the past, much of the research on secretory PLA2s has analyzed their roles in inflammation, anti-bacterial actions and atherosclerosis. In recent studies utilizing a variety of mouse models, pancreatic islets, and clinical trials, a role for many of these enzymes in the control of metabolism and insulin action has been revealed. In this review, this research and the unique contributions of the PLA2 enzymes in insulin resistance and metabolism.